National performance trials for Kenya: Release of Massai and Camello forage grasses - Karimi, Peggy; Mwendia, Solomon; Peters, Michael (2025)
Stakeholders National Variety Release Committee meeting was held at Kenya Plant Health Inspectorate service (KEPHIS) headquarters on 7th June 2025. This was to receive performance and recommendations for release of varieties assessed during National Performance Trials (NPT). The NPT were conducted to evaluate a range of forages including Urochloa spp (Okapi, Mestizo, Camello) and Megathyrus spp (Massai, CIAT 16044, CIAT 688). The Urochloa spp varieties were compared against already released varieties such as Cayman, Cobra and Mulato II while the Megathyrus varieties were checked against themselves. Other Urochloa spp varieties submitted by other organizations were SABIA (Interplant) and SB001 (Simlaw). The aim was to identify suitable candidates for national release to support livestock production through improved forage availability in Kenya. After 2-year evaluation varieties are released based on either of five release criteria